Pembelajaran Tematik dengan Menggunakan Metode Role Playing di Sekolah Dasar - NOVITA, ROZA (Universitas Negeri Padang, 2014)
Abstract The research was conducted as the teacher was not able yet to conduct the learning process of thematic. The aim of this research was to describe the plan, the implementation of the plan, and the students’ learning achievement in the thematic by using Role Playing method. The result of the research indicated that from the first cycle to the second one, the score of the Lesson Plan improved from 71,5 into 85,7, the teacher’s aspect improved from 70,4 into 91,7, and the students’ aspect improved from 66,5 into 90,3. Further, the students’ learning achievement improved from 72,6 into 84. Thus, the use Role Playing method could improve the students’ learning achievement.